Efficiency research of digital switching systems of middle and big capacity - Chaban, Ksenia (Видавництво Львівської політехніки, 2010)
The paper investigated the effectiveness of digital switching systems of modern digital automatic telephone exchanges. Considered as one of the parameters of efficiency - efficiency switching field, which is determined by the number of switching points.
Keywords: switching systems; digital switching module; equivalent switching point